-8-2x+13=11+5x+57

Simple and best practice solution for -8-2x+13=11+5x+57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-2x+13=11+5x+57 equation:


Simplifying
-8 + -2x + 13 = 11 + 5x + 57

Reorder the terms:
-8 + 13 + -2x = 11 + 5x + 57

Combine like terms: -8 + 13 = 5
5 + -2x = 11 + 5x + 57

Reorder the terms:
5 + -2x = 11 + 57 + 5x

Combine like terms: 11 + 57 = 68
5 + -2x = 68 + 5x

Solving
5 + -2x = 68 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
5 + -2x + -5x = 68 + 5x + -5x

Combine like terms: -2x + -5x = -7x
5 + -7x = 68 + 5x + -5x

Combine like terms: 5x + -5x = 0
5 + -7x = 68 + 0
5 + -7x = 68

Add '-5' to each side of the equation.
5 + -5 + -7x = 68 + -5

Combine like terms: 5 + -5 = 0
0 + -7x = 68 + -5
-7x = 68 + -5

Combine like terms: 68 + -5 = 63
-7x = 63

Divide each side by '-7'.
x = -9

Simplifying
x = -9

See similar equations:

| 2x+17=-(3-7x) | | 4-4*5+4= | | 1.64=0.5x-0.2x^2 | | 9x^3+6x^2-9x=0 | | 12-1.5x/3 | | 3y+2=2y+13 | | -1/5b-2/5=-5 | | 250/298=x/368 | | -12a+8=-28 | | N+-4=-11 | | (32b)^(2/3) | | 3•5/13 | | (3x+5)(5x-2)=0 | | 4+2(7r-4)=-116 | | 2=0.15x^2+1 | | (((2z)^(1/5))^4)/(z^(1/20)) | | 4+2(7r-r)=-116 | | 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) | | 2.70=0.55x^2+1 | | -2x-3y=-5 | | -5(4n-4)=40 | | -5h=-20 | | 4(x-1)=2(-x) | | 4p^2+11p-45=0 | | 6(2v-2)=96 | | 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= |

Equations solver categories